Human anatomy - Saladin, Kenneth S. (McGraw-Hill, 2014)
This distinctive text was developed to stand apart from all other anatomy texts with an approach borne out of more than 30 years of teaching, unparalleled art, and a writing style that has been acclaimed by reviewers. Designed for a one–semester college anatomy course, Saladin requires no prior knowledge of chemistry or cell biology.